Severity of the present-day climate in the Polar regions of Siberia - E. V. Maksyutova; L. B. Bashalkhanova (Лëд и снег)
Over the period 1981–2015 severe climatic conditions on the North of Siberia (area within 66–162° E above the Polar Circle) were characterized by significant space-time variations of air temperature at the cold period of the year. This conclusion is made on the basis of analysis of observations made about 13 hour of local time. Positive changes in the mean seasonal air temperature were observed here in October–April. The largest rates of air temperature rise with a pronounced gradient to the West were noted in high latitudes, i.e. in Arctic glacial and polar desert landscapes. The change in weather severity which is one of characteristics of the climate discomfort was analyzed by means of the Arnoldi index (TA). This index reflects the combined effect of negative temperatures and stiff wind on the thermal state of the open surface of the human body. Together with the space-time dynamics of the actual TA values, important values of TA are its threshold values (more than 30 and more than 45 units) which determine a degree of discomfort. Duration of these periods, limiting a possibility of a person's stay in the open air, is also extremely important as well. In recent decades (1981–2015), the spatial differentiation of the number of days (from 80 to 160) limiting the human’s stay in the open air reflects in the main fluctuations of the air temperature and wind regime in polar landscapes. Slight warming (a rise of the air temperature) and small wind speed variability during the period from October to April in 1981–2015 resulted in a certain decrease in the index of weather severity in relation to the period 1966–1980, since the last one did not did not go beyond limit of the interannual variability. Despite the stable increase in the air temperature in 1981–2015, no tendency to reduction of the number of days limiting human’s stay in the open air was noted. The duration of this period for 1981–2015 is similar to that observed in 1936–1964, and we believe that this is suggestive of manifestation of the cyclicity of atmospheric processes and is agreed with a gradual decrease in the rate of the temperature rise. In the last period duration of the period limiting human stay in the open air in the considered area remains high and ranges from 3.5 (to the west of 80° E) to 5 months on islands and capes of the region. So, as is demonstrated by the above example of space-time dynamics of the weather severity index at the time about 13 hours of local time, no decrease in the level of discomfort in polar Siberia is found.